Booming foreign direct investment in R&D: Sectoral and regional composition - Ramachandran, Renjith (Economic and Political Weekly)
India witnessed a massive sixfold jump in foreign direct investment in research and development in 2021. However, its distribution across different industrial sectors and regions was very skewed. Therefore, this article analyses the trends in sectoral composition and spatial distribution of FDI in R&D across Indian cities.- Reproduced
Keywords: Foreign direct investment, R&D